Tourist destinations’ competitiveness: demand and performance factors - Carlyle Tadeu Falcão de Oliveira; Deborah Moraes Zouain; Luiz Alexandre Valadão Souza; André Luís Faria Duarte (Tourism & Management Studies)
This study sought to determine whether tourists and experts have different views on factors that impact tourism in destinations. A qualitative approach was applied using the critical incident technique, which allows respondents to express their specific needs and expectations. The data were collected through open-ended questions. The answers were recorded, and notes were taken about the interviewees and their narratives’ most relevant aspects. The data were then submitted to content analysis and examined by applying the Brazilian competitiveness model. A total of 77 interviews were processed, and 209 critical incidents were identified. The results show that half the critical incidents do not fit into the analysis categories in the Brazilian competitiveness model, so nine ‘new categories’ emerged from the process. Thus, differences exist between visitors’ and experts’ perspectives on what is more important about tourism in destinations